Developing a Simulation of Transformation Geometry by Using Flash - Ahmad, Ahmad; Jaelani, Anton (EDUCARE, 2016)
ABSTRACT: The development of science and technology stimulates the rise of effort to make use of all facilities in all fields. One of the results is increasing number of computer use in Indonesia. This condition encourages educational practitioners to develop several models of learning media by using computers with purposes of tutorial, exercises, simulations, and games. Meanwhile, learning process which applies some media of simulation provides some benefits as they are realistic, secure, and simple. This simulation will lead students into a visualization of real life condition. Without media, students will usually imagine what they learn. It later exposes them with some problems that influence their abstractions. If a lecturer only explains about Transformation Geometry without using simulation, there is a big opportunity that students will yield misconception or they will only remember it with little understanding. This research aims to develop a valid and practical the Transformation Geometry simulation. The method in this research is a design research from a technology perspective that uses a preliminary stage and evaluation stage. The result presented the simulation of the definition of reflection, rotation, rotation half-round, and translations that have been made are in accordance with the curriculum and the existing concepts. Try-out result shows that the simulation can help students find their own concepts of reflection, rotation, rotation half-round, and translation; and sets up students to communicate. The conclusion of this research is that the result of simulation design that has been created has to be valid and practical.KEY WORDS: Development of Science and Technology; Computer Use; Transformation Geometry; Learning Process; Understanding of Concepts.Â Â About the Authors: Ahmad and Anton Jaelani are the Lecturers at the Department of Mathematics Education, Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto, Central Java, Indonesia. Corresponding authors is: ahmadump@yahoo.co.idHow to cite this article? Ahmad & Anton Jaelani. (2016). âDeveloping a Simulation of Transformation Geometry by Using Flashâ in EDUCARE: International Journal for Educational Studies, Vol.8(2) February, pp.129-138. Bandung, Indonesia: Minda Masagi Press and UMP Purwokerto, ISSN 1979-7877. Chronicle of the article: Accepted (January 17, 2016); Revised (February 1, 2016); and Published (February 28, 2016).